Open access research outputs receive more diverse citations - Huang, Karl; Neylon, Cameron; Montgomery, Lucy; Hosking, R.; Diprose, J.P.; Handcock, Rebecca; Wilson, Katie (2024)
The goal of open access is to allow more people to read and use research outputs. An observed association between highly cited research outputs and open access has been claimed as evidence of increased usage of the research, but this remains controversial. A higher citation count also does not necessarily imply wider usage such as citations by authors from more places. A knowledge gap exists in our understanding of who gets to use open access research outputs and where users are located. Here we address this gap by examining the association between an output’s open access status and the diversity of research outputs that cite it. By analysing large-scale bibliographic data from 2010 to 2019, we found a robust association between open access and increased diversity of citation sources by institutions, countries, subregions, regions, and fields of research, across outputs with both high and medium–low citation counts. Open access through disciplinary or institutional repositories showed a stronger effect than open access via publisher platforms. This study adds a new perspective to our understanding of how citations can be used to explore the effects of open access. It also provides new evidence at global scale of the benefits of open access as a mechanism for widening the use of research and increasing the diversity of the communities that benefit from it.